Enhancing reactive blue 4 adsorption through chemical modification of chitosan with hexadecylamine and 3-aminopropyl triethoxysilane - Vakili, M. (Elsevier Ltd, 2017)
The adsorption of dye on chitosan and its derivatives is considered as an alternative and environmentally friendly method. Nevertheless, chemical modification of chitosan can lead to a more suitable adsorbent. In this study, the adsorption performance of chemically modified chitosan beads using a cationic surfactant (hexadecylamine) and an organo-silane (3-aminopropyl triethoxysilane) was studied for removal of reactive blue 4 (RB4) dye from aqueous solution. The chemical structure, surface properties and morphology of modified chitosan beads were analysed using FTIR, SEM and zeta-potential techniques. Results revealed that the adsorption of the RB4 was more favored in acidic conditions (pH 4). After modification adsorption capacity of chitosan beads increased for 1.48 times. The maximum adsorption capacity of chitosan beads increased from 317.1 mg/g to 468.8 mg/g after modification. This increase was attributed to the increase in the positive charge of modified chitosan beads. The experimental data obtained from adsorption of RB4 onto unmodified and modified chitosan confirmed a better fitness to Freundlich isotherm model (R2 = 0.946 and 0.892, χ2 = 22.414 and 45.62) as compared to Langmuir model (R2 = 0.894 and 0.777, χ2 = 138.301 and 47.08). It was concluded that chemical modification is a suitable method to improve the anionic dye adsorption efficiency of chitosan beads. © 2016 Elsevier Ltd